The mediating role of sexually selected traits in the association of androgynous tendencies with lower sexual activeness among Chinese youths - Zhao, Shuangyu; Guo, Fuyu; Hee, Jia Yi; Tang, Kun (Frontiers in Psychology, 2022)
Androgynous tendencies and persistently low fertility rates have been observed in many countries, causing major social concerns. The theory of sexual selection suggests a possible mechanism between androgyny and decreased sexual activeness, as masculinity and femininity constitute an important aspect of reproductive strategies. This theory has also been proven by evolutionary and societal evidence. Therefore, we investigate the association between masculinity and femininity with sexual activeness, as well as the influence of gender-role conformity on the frequency of sexual intercourse through sexually selected traits among 42,492 Chinese youths. Sexual activeness was measured using sexual attitudes, experience, behaviors, and pleasure. Mediation analysis was employed to investigate the effects of sexually selected traits on the association between masculinity and femininity with sexual activeness, and gender-role conformity with the frequency of sexual intercourse. Low sexual activeness was found to be associated with low gender-role conformity. Our findings also suggest that physical attractiveness, sexual motivation, and interpersonal relationships may mediate the association between sexual activeness and gender-role conformity, supporting the males-compete/females-choose model.